Music and Melody-based Elementary School Mathematics Learning: Correlational Study of Student Learning Outcomes Achievement - Tomy Agung Sugito; Ali Fakhrudin (Edumaspul: Jurnal Pendidikan, 2024)
Choosing a learning strategy is very important to get optimal learning results, providing motivation and interest in learning for students in learning mathematics in elementary school. The implementation of music and melodies in learning can be used as a solution strategy to provide a positive impact on learning in creating and increasing creativity, self-confidence, motivation and cognitive skills. Apart from that, the strategy of using music in learning is an effective strategy to implement so that students can learn independently. For this reason, this study investigates the impact of music and melody teaching on lower grade elementary school mathematics learning outcomes. This research uses a quasi-experimental design with an experimental design and a control group. The statistical population includes 120 third grade students selected as the research sample. Both groups learn the same things and defined concepts. However, the experimental group learned these concepts using music and melody teaching, while the control group learned these concepts using conventional-based teaching methods and students' final mathematics scores were used in the analysis. Questionnaires, motivational questionnaires, learning outcomes tests are used in research instruments. The results of covariance analysis show that teaching mathematics using music and melody methods has a significant positive impact on elementary school students' mathematics learning, namely (87.3%) and increases student learning motivation by (92%). Therefore, it can be concluded that applying melodic teaching in learning mathematical concepts can be more effective than conventional teaching methods.